Prevalence and Characteristics of Dental Erosion in Swimmers in Muang Districts, of Khon Kaen and Mahasarakham - Visavakul, Chalinthorn; Pitiphat, Waranuch; Rattanacharoenthum, Anoma; Kitsahawong, Kemporn (Khon Kaen University Dental Journal, 2019)
In Thailand, there are reports of tooth erosion among swimming athletes and regular swimmers. The most common problem related to tooth erosion is tooth hypersensitivity, leading to the negative effects on daily life. The purpose of this cross-sectional study was to evaluate the prevalence and characteristics of tooth erosion as well as its related factors among swimmers aged 13-25 years in Muang District, Khon Kaen and Mahasarakham Provinces, Thailand. Clinical examinations including the measurements of tooth erosion, dental caries experience, and oral hygiene were performed by one calibrated dentist. The Basic Erosive Wear Examination was used to evaluate the level of erosion on six upper anterior teeth. The pH of pool water was measured. Related information was collected using self-administered questionnaire. The data were analyzed by using descriptive statistics and Kruskal-Wallis Test was used to compare the relation between the number of years of regularly practicing swimming and tooth erosion. The results from 46 swimmers showed that the mean debris score of this population was 1.3±0.5. The prevalence of tooth erosion and sudden tooth hypersensitivity after swimming was 100%. The most severe erosive teeth were central incisors, followed by lateral incisors and canines, respectively. Erosive defects were more severe on labial surfaces than palatal surfaces. Swimmers who had practiced swimming for longer years tended to have more severe tooth erosion (p=0.05). In addition, the difference of mean erosion score of buccal surfaces was statistically significant (p=0.01). Therefore, health education on the prevention of dental erosion in swimmers should be considered.